Cystic adventitial degeneration of common femoral artery: An unusual case of intermittent claudication. Case report and literature review - Gabriele Pagliariccio; Di Ilenia Sario; Filippo Gianfelice; Antonio Villani; Alberto Giansante; Enrico Franceschini; Guido Baiocchi; Vinicio Rizza; Luciano Carbonari (Annals of Vascular Surgery - Brief Reports and Innovations, 2022)
Non atherosclerotic diseases producing intermittent claudication in middle-aged men are rare, but they are an important minority. Cystic adventitial disease (CAD) is one of these entities; its more frequent location is the popliteal artery. We describe an unusual case of CAD involving common femoral artery in young. Early and careful diagnosis (by Doppler Ultrasonography or Computed Tomography Angiography) and prompt repair appear crucial to achieve good outcomes. The diagnosis was made during the surgical procedure carried out for severe intermittent claudication. Surgical treatment with total excision of the lesion and arterial reconstruction with PTFE prothesis provides a complete resolution of the symptoms. We review the literature about non-atherosclerotic causes of lower extremity claudication, describing etiology, diagnosis and treatment. Conditions including popliteal artery entrapment syndrome, pseudoxanthoma elasticum, iliac fibromuscular disease, persistent sciatic artery, iliac/femoral giant cell arteritis and iliac endofibrosis are described. As the low incidence of these lesions and the poor literature data, the authors suggest that all patients with intermittent claudication without atherosclerotic disease should be investigated to look for these syndromes.